+0

# Eliminate the parameter t to find a simplified Cartesian equation of the form y = m x + b for {(x(t)= 5 - t),(y(t) = 2 - 4 t) :}

0
882
1

Eliminate the parameter t to find a simplified Cartesian equation of the form y = m x + b for {(x(t)= 5 - t),(y(t) = 2 - 4 t) :}

The Cartesian equation is y =

Guest Jun 4, 2015

#1
+82757
+10

x(t)  = 5 - t   →    t  = 5 - x

y(t)  =  2 - 4t    so we have, by substitution...

y(x)  = 2 - 4(5 - x)   →   y = 2 - 20 + 4x    →   y = 4x - 18

Here's a graph of both forms......the lines overlay each other........https://www.desmos.com/calculator/fahnek1aoa

CPhill  Jun 4, 2015
Sort:

#1
+82757
+10

x(t)  = 5 - t   →    t  = 5 - x

y(t)  =  2 - 4t    so we have, by substitution...

y(x)  = 2 - 4(5 - x)   →   y = 2 - 20 + 4x    →   y = 4x - 18

Here's a graph of both forms......the lines overlay each other........https://www.desmos.com/calculator/fahnek1aoa

CPhill  Jun 4, 2015

### 33 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details